The Negative Influence of Viral Marketing and Brand Awareness on Customer Trust and Purchase Decisions of Pro-Israel Products in Banten Province - Huddin, Muhammad Nurhaula; Nafiudin, Nafiudin; Jadmiko, Purbo; Abduh, Muhamad; Saadah, Fitriatus (Department of Islamic Economics, IPB University, 2025)
This study investigates the influence of viral marketing, brand awareness, and trust on the purchase decisions of pro-Israel products in Banten Province. Anchored in the Stimulus-Organism-Response (SOR) theory, the research conceptualizes viral marketing and brand awareness as external stimuli (S), consumer trust as the internal organismic state (O), and purchase decisions as the behavioural response (R). The study employs a purposive sampling technique targeting individuals who previously purchased pro-Israel products but have since discontinued or become more selective in their choices. Data were collected through an online survey involving 278 respondents and analyzed using Structural Equation Modelling (SEM) with AMOS 23. The results indicate that viral marketing and brand awareness have a significant negative effect on consumer trust. Furthermore, viral marketing, brand awareness, and trust each have a negative influence on purchase decisions regarding pro-Israel products. These findings underscore the mediating role of trust within the SOR framework, highlighting how consumer perceptions shaped by external marketing stimuli impact ethical decision-making. The study concludes that brands operating in sensitive socio-political contexts must carefully manage their marketing communications to maintain trust and consumer alignment. These insights provide valuable implications for marketers aiming to influence behaviour through ethical and culturally sensitive branding strategies.